Overall coordination fitness in football: rating criteria - Gorskaya, I. Y.; Averyanov, I. V.; Mironenko, E. N. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to develop quantitative criteria for evaluation of the level of development of coordination abilities in 9-17 year-old football players to improve the training process control and correction model. Methods and structure of the study. The level of coordination preparedness of the football players was assessed using the standard methods currently applied by the researchers (stabilography, psychomotor and pedagogical testing). We also used the methods of mathematical modeling and statistics. Sampled for the study were 258 football players aged 9-17 years (qualification levels: Candidate Master of Sports, 1st-3rd senior categories).